2003
DOI: 10.1140/epje/i2002-10117-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a new lipid/DNA complex showing a selective transfection efficiency in ovarian cancer cells

Abstract: We investigated, for the first time, by using Energy Dispersive X-ray Diffraction, the structure of a new ternary cationic liposome formulated with dioleoyl trimethylammonium propane (DOTAP), 1,2-dioleoyl-3-phosphatidylethanolamine (DOPE) and cholesterol (Chol) (DDC) which has been recently found to have a selective high gene transfer ability in ovarian cancer cells. Our structural results provide a further experimental support to the widely accepted statement that there is not a simple and direct correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 0 publications
0
38
0
Order By: Relevance
“…Cationic lipids and cationic polymers have been extensively studied for gene transfer experiments, during the last two decades [4][5][6][7][8][9] . In spite of a few limitations, such as a relatively low transfection rate and some intrinsic cell toxicity, these cationic agents are considered as a valid alternative to viral vectors [10][11][12]. Indeed, cationic polymers and liposomes are generally non-immunogenic, easy to produce, and non-oncogenic.…”
Section: Introductionmentioning
confidence: 99%
“…Cationic lipids and cationic polymers have been extensively studied for gene transfer experiments, during the last two decades [4][5][6][7][8][9] . In spite of a few limitations, such as a relatively low transfection rate and some intrinsic cell toxicity, these cationic agents are considered as a valid alternative to viral vectors [10][11][12]. Indeed, cationic polymers and liposomes are generally non-immunogenic, easy to produce, and non-oncogenic.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In acute dermal and epidermal wounds, liposomal gene transfer of genes coding for growth factors was shown effective in improving dermal and epidermal regeneration. 1,[5][6][7] Therefore, we used the physiologic cascade of wound healing as a model to investigate the effect of non-viral liposomal gene transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Some earlier studies suggested that the inverted hexagonal phase leads to more efficient transfection efficiency than does the lamellar phase (13,14). Recent experiments dispute this suggestion, however, and there is considerable evidence against a direct general correlation between lipoplex structure and transfection efficiency (15)(16)(17)(18)(19)(20)(21). Furthermore, a viewpoint now emerging is that the critical factor in lipid-mediated transfection is the structural evolution of lipoplexes upon interacting and mixing with cellular lipids (7)(8)(9).…”
mentioning
confidence: 99%